Wideband polarization-insensitive metamaterial absorber with perfect dual resonances - Ayop, Osman (Springer Verlag, 2016)
This paper presents the analysis of wideband polarization-insensitive metamaterial absorber with perfect dual resonances. The structure is designed using lossy FR4 substrate with copper layers. The resonating elements are designed using the combination of circular ring with modified circle-shaped structure. The resonating elements are printed on the top surface of FR4 substrate, while the bottom surface is printed with full copper ground plane. From the simulation, the proposed design achieves nearly perfect absorbance at dual resonant frequency with improved bandwidth compared to the general circular ring design. Two peaks absorbance of 98.66 and 99.84 % are observed at 9.81 and 10.41 GHz respectively with full width half maximum (FWHM) bandwidth of 1050 MHz or 10.38 % at normal incident EM wave. The structure is also simulated for different polarization angles and it is observed that the structure can maintain the absorbance characteristic for all polarization angles. The experimental work is done to validate the simulated result. It is confirmed that two peaks absorbance are achieved with magnitudes of 99.88 and 99.67 % at 10.14 and 10.79 GHz, respectively. The measured FWHM is 1160 MHz.